Socioemotional wealth in volatile,uncertain, complex and ambiguous contexts: The case of family firms in Latin America and the Caribbean - Gómez Mejía, Luis; Mendoza López, Anabel; Duran, Patricio; Aguinis, Herman; Cruz, Cristina (Elsevier Ltd, 2024)
The paradoxical nature of Latin America and the Caribbean (LAC) provides unique opportunities to advance management theory. Focusing on a dominant theoretical framework,Socioemotional Wealth (SEW),we argue that contextual features of LAC,namely the concept of extended family and the volatile,uncertain,complex,and ambiguous (VUCA) environment,make family businesses “SEW intensive” (i.e.,high degree of preservation and enhancement of various aspects of SEW) and “SEW sensitive” (i.e.,high degree of firm responsiveness to external factors that are SEW-relevant). In turn,these SEW features influence decision making and approaches to dealing with performance hazards and venturing risks. While we use LAC as a specific context,our theorizing and 12 propositions are also relevant to guide future research on other regions of the world,such as parts of Africa,Asia,and the Middle East,where the concept of extended family is widespread and a VUCA environment is also predominant. Overall,we use the characteristics of the LAC context to challenge existing assumptions,advance theory,and guide future empirical research on family businesses. © 2023 The Authors
Keywords: Entrepreneurship; Family business; Latin America and the Caribbean; Management theory; Socioemotional wealth; Theory advancements; VUCA; 53 Ciencias Económicas; ODS 16 - Paz, justicia e instituciones sólidas